Diffusion microscopic MRI of the mouse embryo: Protocol and practical implementation in the splotch mouse model. Issue 2 (13th March 2014) - Norris, Francesca C.; Siow, Bernard M.; Cleary, Jon O.; Wells, Jack A.; De Castro, Sandra C.P.; Ordidge, Roger J.; Greene, Nicholas D.E.; Copp, Andrew J.; Scambler, Peter J.; Alexander, Daniel. C.; Lythgoe, Mark F.
<x xml:space="preserve">Abstract</x> Purpose Advanced methodologies for visualizing novel tissue contrast are essential for phenotyping the ever‐increasing number of mutant mouse embryos being generated. Although diffusion microscopic MRI (μMRI) has been used to phenotype embryos, widespread routine use is limited by extended scanning times, and there is no established experimental procedure ensuring optimal data acquisition. Methods We developed two protocols for designing experimental procedures for diffusion μMRI of mouse embryos, which take into account the effect of embryo preparation and pulse sequence parameters on resulting data. We applied our protocols to an investigation of the splotch mouse model as an example implementation. Results The protocols provide DTI data in 24 min per direction at 75 μm isotropic using a three‐dimensional fast spin‐echo sequence, enabling preliminary imaging in 3 h (6 directions plus one unweighted measurement), or detailed imaging in 9 h (42 directions plus six unweighted measurements). Application to the splotch model enabled assessment of spinal cord pathology. Conclusion We present guidelines for designing diffusion μMRI experiments, which may be adapted for different studies and research facilities. As they are suitable for routine use and may be readily implemented, we hope they will be adopted by the phenotyping community. Magn Reson Med 73:731–739, 2015. © 2014 Wiley Periodicals, Inc.